2022
DOI: 10.1590/fst.116221
|View full text |Cite
|
Sign up to set email alerts
|

Effects of taro powder on the properties of wheat flour and dough

Abstract: This work aimed to investigate the effect of taro powder on the quality of wheat flour products. The water and starch content, whiteness, pasting properties, texture, microstructure, rheological properties of dough and water distribution in dough were analyzed. Taro powder significantly increased the peak viscosity, trough viscosity, final viscosity and setback value in the gelatinization process of flour, reduced the breakdown value, and increased the gelatinization temperature. Taro flour showed the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…This result indicated that lower addition of WQF (less than 20%) and fermentation improved the elasticity and rigidity of mixed flour dough to some extent; however, higher addition of WQF (more than 20%) led to an inverse trend that decreased the dough elasticity and rigidity. Similar conclusions had also been reported by Zhang et al (2016) and Zuo et al (2022). In Figures 2(b) and 2(c), as compared to sample C, the dough extensibility and energy value of mixed flour exhibited a similar trend which decreased from 145.0 ± 1.0 to 91.0 ± 4.2 min as WQF was added in the mixed flour.…”
Section: Extensographical Parameterssupporting
confidence: 91%
See 2 more Smart Citations
“…This result indicated that lower addition of WQF (less than 20%) and fermentation improved the elasticity and rigidity of mixed flour dough to some extent; however, higher addition of WQF (more than 20%) led to an inverse trend that decreased the dough elasticity and rigidity. Similar conclusions had also been reported by Zhang et al (2016) and Zuo et al (2022). In Figures 2(b) and 2(c), as compared to sample C, the dough extensibility and energy value of mixed flour exhibited a similar trend which decreased from 145.0 ± 1.0 to 91.0 ± 4.2 min as WQF was added in the mixed flour.…”
Section: Extensographical Parameterssupporting
confidence: 91%
“…Glutenin in wheat flour gives gluten good elongation, and gliadin gives gluten good elasticity (Diego and Alba, 2020). The energy value represents the total energy it takes to stretch the dough from the beginning until it breaks; a higher energy represents a stronger dough (Zhang et al, 2016). The addition of non-gluten flour such as WQF will dilute the gluten protein network, and cannot form a network that is strong enough to finish the latter process such as fermentation and heating, especially for a higher amount addition of WQF.…”
Section: Extensographical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, for further study, the supporting phase and the oscillating phase can be divided into eight stages as shown in FIG. 2 below [2].…”
Section: Exoskeleton Dynamics Analysis 1motor Gaitmentioning
confidence: 99%
“…Cellulose, pectin and other substances in fruit and vegetable powder can affect the intermolecular arrangement of starch and change the characteristics and structure of starch gel (Correa & Ferrero, 2015). Therefore, in many researches fruit and vegetable powder is added in flour products to develop products with better properties (Zhang et al, 2022). When the ratio of Chinese yam powder to low-gluten flour was 1:5, the contents of fat and fast-digestible starch were significantly reduced, while the contents of flavonoids, resistant starch, slow-digestible starch and protein were significantly increased to meet the market demand (Yalindua et al, 2021;Kurek & Sokolova, 2020).…”
Section: Introductionmentioning
confidence: 99%